Synthesis and biomechanistic studies of quinocarcin and structural analogs - Flanagan, Mark Edward, author; Williams, Robert M., advisor (Colorado State University. Libraries, 1995)
The formal total synthesis of the antitumor antibiotic quinocarcin is presented. The synthesis is characterized by a novel NBS oxidative azomethine ylide cycloaddition reaction for the diastereoselective construction of the tetracyclic framework of this substance. A novel mechanism for the reduction of molecular oxygen that results in the O2-dependent cleavage of DNA by quinocarcin, tetrazomine and synthetic structural analogs is presented. The results are discussed in the context of a redox self-disproportionation of the oxazolidine moieties of these compounds which produces superoxide by a previously unrecognized mechanism discovered herein. Stereoelectronic control elements of superoxide production have been elucidated through the use of structural analogs prepared by total synthesis. The synthesis of a structurally less complex water soluble analog of quinocarcin which exhibits most of the physical properties associated with the parent compound is presented. By covalently attaching known DNA binding molecules to this substance, the ability to vary the mechanism and DNA-cleavage specificity of this compound has been demonstrated and is presented herein along with a proposed binding model derived from molecular mechanics.
Keywords: Antineoplastic antibiotics; Carcinogens